A4.10 Hydrogen Sulfide Attenuates Store-Operated Ca2+ Entry In Endothelial and Smooth Muscle Cells. (25th February 2013) - Kloesch, B; Stranimaier, S; Steiner, G; Schmidt, K
Abstract : Background and Objectives: Endothelial cells are active participants in inflammatory processes. They are involved in diverse activities including the regulation of leucocyte extravasation, angiogenesis, cytokine production, protease and extracellular matrix synthesis, vasodilation, etc. The small gaseous molecule hydrogen sulphide (H2 S) is involved in a variety of physiological processes like vascular relaxation, angiogenesis, neurotransmission and inflammation. In the vascular system, ATP-sensitive K + -channels are a major target for H2 S but over the last few years evidence has accumulated that several Na + - and Ca 2+ -permeable channels are also sensitive to H2 S. In the present study we investigated the effect of H2 S on Ca 2+ signalling in cultured endothelial and smooth muscle cells with special emphasis given to the role of H2 S in modulating store-operated Ca 2+ channels. Materials and Methods: Experiments were performed with human microvascular endothelial cells (HMEC-1), endothelial cells isolated from porcine aorta, and smooth muscle cells isolated from rat aorta and rat trachea. Mobilisation of intracellular Ca 2+ and Ca 2+ entry was monitored by measuring the intracellular free Ca 2+ concentration with FURA-2 in the absence and presence extracellular Ca 2+, respectively. Activity of endothelial nitric oxide synthase (eNOS) in intact cells was determined as conversion of incorporated L-[ 3 H]-arginine into L-[ 3 H]-citrulline. Results: Incubation of human and porcine endothelial cells with the H2 S-donor NaHS (100 µM, 10–45 min) evoked a release of Ca 2+ from intracellular stores that was not accompanied by Ca 2+ influx from the extracellular space. In accordance with these data suggesting that H2 S may inhibit store-operated Ca 2+ entry, incubation of cells with NaHS attenuated Ca 2+ influx induced by depletion of Ca 2+ stores with receptor agonists (ATP, histamine) or the endoplasmatic reticulase ATPase inhibitor, thapsigargin. As a consequence, the stimulatory effect of these agonists on endothelial NO formation was strongly diminished, whereas the response to the Ca 2+ ionophore A23187 was barely affected. Similar to the results obtained with endothelial cells, depletion of intracellular Ca 2+ stores in smooth cells isolated from rat aorta or rat trachea also resulted in a pronounced Ca 2+ entry that was completely blocked upon pre-treatment of cells with NaHS. Conclusions: H2 S inhibits the stimulatory effect of Ca 2+ of mobilising agonists on endothelial NO formation by attenuating store-operated Ca 2+ entry. Inhibition of store-operated Ca 2+ channels by H2 S is not peculiarity of endothelial cells but also occurs in vascular and tracheal smooth muscle cells. These hitherto undescribed effects may be in part possible for the beneficial effects of H2 S in sulphur bath therapy.